2021
DOI: 10.3389/fimmu.2021.742631
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Antibody-Dependent Cellular Cytotoxicity in a Spanish Cohort of Patients With COVID-19 Admitted to the ICU

Abstract: SARS-CoV-2 infection causes COVID-19, ranging from mild to critical disease in symptomatic subjects. It is essential to better understand the immunologic responses occurring in patients with the most severe outcomes. In this study, parameters related to the humoral immune response elicited against SARS-CoV-2 were analysed in 61 patients with different presentations of COVID-19 who were recruited in Hospitals and Primary Healthcare Centres in Madrid, Spain, during the first pandemic peak between April and June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“… 9 , 17 Another ex vivo study analyzed the potential of peripheral blood mononuclear cells derived from patients with COVID-19 to induce an ADCC response against rituximab-coated Raji cells. 18 The authors found a considerably defective ADCC response in hospitalized patients with COVID-19, which also shows exhaustion of ADCC mediating cells in these patients. Combined, these and our data show that the SARS-CoV-2-specific antibody-mediated ADCC responses may contribute to the immune exhaustion in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 95%
“… 9 , 17 Another ex vivo study analyzed the potential of peripheral blood mononuclear cells derived from patients with COVID-19 to induce an ADCC response against rituximab-coated Raji cells. 18 The authors found a considerably defective ADCC response in hospitalized patients with COVID-19, which also shows exhaustion of ADCC mediating cells in these patients. Combined, these and our data show that the SARS-CoV-2-specific antibody-mediated ADCC responses may contribute to the immune exhaustion in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 95%
“…Cellular cross-reactivity against EBV and SARS-CoV-2 has not been studied to date. However, there have been reports associating the clinical manifestation of COVID-19 with reactivation of EBV infection and correlating it with severe disease progression, thus underpinning a possible entanglement [70][71][72] . Cross-reactivity between SARS-CoV-2 and HIV has also been reported in studies describing false positive HIV results in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, PCR testing was repeated periodically [ 14 , 16 , 17 , 56 ]. Regarding serology, anti-HSV-1 IgG levels in patients with severe and critical COVID-19 have been reported to be 4.6 and 6 times higher than in healthy subjects, respectively [ 59 ]. In the same study, anti-HSV-1 IgG levels in patients with critical COVID-19 were two times higher than in patients with mild COVID-19 [ 59 ].…”
Section: Methodsmentioning
confidence: 99%